2017
DOI: 10.1112/s0025579317000250
|View full text |Cite
|
Sign up to set email alerts
|

Tighter Bounds for the Discrepancy of Boxes and Polytopes

Abstract: Abstract. Combinatorial discrepancy is a complexity measure of a collection of sets which quantifies how well the sets in the collection can be simultaneously balanced. More precisely, we are given an n-point set P, and a collection F = {F 1 , . . . , F m } of subsets of P, and our goal is color P with two colors, red and blue, so that the maximum over the F i of the absolute difference between the number of red elements and the number of blue elements (the discrepancy) is minimized. Combinatorial discrepancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The last line follows by Bansal and Garg [3] showed disc(n, R d ) = O(log d n), and their proof provides a polynomial time algorithm. Nikolov [25] soon after showed that disc(n, R d ) = O(log d− 1 2 n) although this result does not describe how to efficiently construct the coloring. With these result we obtain the following.…”
Section: Gaussian Kernel Coresets Bounded Using Rectangle Discrepancymentioning
confidence: 99%
“…The last line follows by Bansal and Garg [3] showed disc(n, R d ) = O(log d n), and their proof provides a polynomial time algorithm. Nikolov [25] soon after showed that disc(n, R d ) = O(log d− 1 2 n) although this result does not describe how to efficiently construct the coloring. With these result we obtain the following.…”
Section: Gaussian Kernel Coresets Bounded Using Rectangle Discrepancymentioning
confidence: 99%
“…Theorem 1.1 was also used in a very interesting non-black box way in a later work by Banaszczyk [Ban12] to show improved bounds for several variants of the Steinitz problem. Recently, [Nik17] used this to obtain improved bounds for the Tusnady's problem.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this success, Banaszczyk's more recent results on signed series [3], and the last author's upper bounds on the discrepancy of axis-aligned boxes [27], both proved using the techniques used in [2], remain out of reach algorithmically. Extending the techniques of this paper and of [6] to give constructive proofs of these results is an interesting open problem.…”
Section: Conclusion and Follow-up Workmentioning
confidence: 99%